PENGARUH TRANSFORMATIONAL LEADERSHIP TERHADAP WORK ENGAGEMENT DENGAN MEANING IN WORK SEBAGAI VARIABEL INTERVENING (Studi Pada ASN Kantor Pelayanan Kekayaan Negara dan Lelang Semarang) - Sari, Adellia Anggita; Andriyani, Andriyani (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT Human resources have an important role in achieving company goals, development and empowerment aims to make employees have good performance. Good employee performance determines success, whereas poor employee performance determines failure in achieving company goals. One of the efforts to improve employee performance is to foster employee work engagement. Work engagement is an important issue to be researched. This study aims to analyze the influence of transformational leadership on work engagement which is mediated by meaning in work at one of the government agencies in Semarang, namely the Semarang State Property and Auction Service Office (KPKNL). This study used primary data distributed through questionnaires to civil servants at the Semarang State Property and Auction Services Office as research samples, and secondary data obtained from articles, journals, theses, books, and other relevant sources. The number of samples used in this study were 44 respondents using census techniques. The data analysis technique uses the SmartPLS 3.0 application to test the hypotheses and the influence between these variables. This questionnaire was developed by researchers using a 5 Likert scale. The results in this study indicate that transformational leadership has a positive influence on work engagement. This study also shows that there is an influence of meaning in work as a mediating variable between transformational leadership and work engagement.